A Legal Protection Of Children With Disabilities In Access To Medical Cannabis Treatment (Case Study Of Pika Sasikirana And Comparison With The Legalization Of Medical Marijuana In Thailand) - Cut Sara Devariza Azhari (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The objective of this study is to describe the regulation of marijuana in Indonesia and Thailand and examine the impact of marijuana legalization policies in Indonesia and Thailand. This research uses normative legal research, with statutory, and comparative approaches. The results of this study indicate that the regulation of marijuana in Indonesia and Thailand has been regulated through the Narcotics Code B.E. 2564 of 2021, while in Indonesia, marijuana is regulated in Law Number 35 of 2009 concerning Narcotics. Marijuana plants in Indonesia were until now considered haram and disadvantageous. The impact of legalizing medical marijuana in Thailand has advantages in various sectors, such as economic, social, and health. When compared to Indonesia, Indonesia has not yet legalized the use of marijuana for several reasons, including its negative impact, whereas when viewed in terms of what occurs in the community, marijuana can be used as a medicinal material.